IMPROVING THE STUDENTS’ SPEAKING ABILITY THROUGH CASE PRESENTATION METHOD - Dzur Rif'ah Mahmudah (Universitas Muhammadiyah Makassar, 2015)
The research aimed at finding out the improvement of students’ speaking ability through Case Presentation at the eleventh grade of SMA Negeri 1 Libureng Bone. The method of this research was classroom action research that consisted of two cycles. One cycle consisted of four meetings. It means that there were eight meeting in two cycles. This classroom action research was done at SMA Negeri 1 Libureng Bone for English subject. The subject research was 39 students of senior high school in 2012-2013 academic years. Those consist of 26 women and 13 men. Instruments are speaking test and observation sheet. The findings of this research were the improvement of the students’ speaking ability in terms of speaking accuracy and speaking fluency in which the mean score of diagnostic test was 5.30, the mean score of cycle I was 6.27 and the mean score of cycle II was 7.29. The result above indicated that there was significant improvement of the students’ speaking ability in terms of speaking accuracy and speaking fluency in the application of case presentation method at the eleventh grade of SMA Negeri 1 Libureng Bone.